Czechoslovak Architecture in Subcarpathian Rus - Loutocká, Vlasta (Vysoké učení technické v Brně, Fakulta architektury, 2024)
This paper deals with an outline of the doctoral student’s research work. It briefly lists some of the most important buildings left by Czechoslovak architects in Subcarpathian Rus in the interwar period.
Keywords: Interwar architecture, Subcarpathian Ruthenia, Czechoslovak architects, residential and civil buildings, urban planning